THE NEW CAPITAL ADEQUACY FRAMEWORK (BASEL III) OPTIONS AND ISSUES IN COMMERCIAL BANKS OF LITHUANIA - Jasevičienė, Filomena; Jurkšaitytė, Daiva (Ekonomika, 2015)
Currently, banking is one of the most regulated activities in the world, because banks are the most important institutional units engaged in financial intermediation and affects not only the whole national economy of the country, but the global financial market as well. One of the key components of banking regulation are requirements expected for the bank capital, which prevent the bank from various unforeseen risks incurring substantial losses and are a sort of guarantee to maintain the financial system stability. For this reason, it is useful to find out what factors affect the capital adequacy ratio, and what measures the banks are going to take in order to meet the new capital requirements. The present research reveals the options of the implementation of the new system and the main problems faced by banks. The paper consists of four main parts: review of theory and literature, the research methodology of the factors influencing the capital adequacy, the study of factors influencing the capital adequacy ratio, and the capital adequacy management problem areas according to the Basel III requirements and conclusions.
Keywords: banks; supervision; capital adequacy rates; capital structure; accepted risks